Restructuring through spin‐off or sell‐off: transforming information asymmetries into financial gain - Bergh, Donald D.; Johnson, Richard A.; DeWitt, Rocki-Lee (Strategic Management Journal, 2007)
Abstract The authors examine how managers select between corporate restructuring implementation alternatives and how those decisions influence the profitability of the restructuring event. They argue that managers and owners have information asymmetries with respect to the assets in the restructuring and the restructured firms' diversification strategy, and that managers select between two popular implementation alternatives, spin‐offs and sell‐offs, to convert knowledge differences into financial gain. When the restructured assets reside in primary and related business lines or the firm has low and related diversification among its business lines, the restructuring is difficult for observers to assess and understand. Spin‐offs most effectively and profitably reduce information asymmetries by transferring assets to the capital market and increasing the efficiency and transparency of the restructuring firm. Conversely, when the restructured assets reside in secondary and unrelated business lines or the firm has high diversification, sell‐offs best mitigate asymmetries by using market forces to reallocate assets to their most productive uses while improving the strategy and performance of the restructuring firm. Tests of a sample of 204 restructuring events support the hypotheses. Overall, the findings suggest that the influence of corporate restructuring on financial performance is determined in part through how the restructuring is implemented. Copyright © 2007 John Wiley & Sons, Ltd.